Families of Victims Often Reject Forensic Autopsies in Cases of Unnatural Death - Slamet, Amalul Arifin; Sambas, Nandang; Mahmud, Ade (Sinergi International Journal of Law, 2024)
Forensic autopsies are integral to determining the exact cause of someone's death. In Indonesian criminal law, specifically Articles 222 of the Criminal Code and Articles 133-134 of the Criminal Procedure Code (KUHAP), provisions regarding forensic autopsies are outlined. However, there are challenges in implementing the requirement to notify the victim's family about the autopsy, which can hinder the enforcement of law in cases of unnatural deaths. It's crucial to note that only through forensic autopsies can material truths be scientifically revealed, from the initiation of investigations to the presentation of evidence in court. Legal cases and final court decisions underscore the importance of forensic autopsies in proving cases categorized as material criminal offenses. Therefore, in cases of unnatural deaths, the execution of forensic autopsies should not necessarily depend on the victim's family consent to ensure fair legal certainty for all parties involved - the victim, perpetrator, and society. This study aims to understand the role of forensic autopsies in unnatural deaths and examine cases where the victim's family rejects the autopsy based on Article 222 of the Criminal Code in conjunction with Articles 133-134 of the Criminal Procedure Code. The research methodology combines normative and empirical approaches to analyze applicable legal norms and their application in events to achieve predefined objectives. Findings indicate that the refusal of the victim's family to consent to a forensic autopsy in unnatural deaths significantly impacts court decisions, potentially obstructing law enforcement agencies in resolving cases. Even if the family objects, law enforcement agencies must continue their duties, as forensic autopsies are vital for court evidence, typically presented as a report issued by forensic experts or doctors under police instruction. During trials, victims can still attain legal certainty and justice. Forensic autopsies should align with existing laws. It is hoped that from this research the implementation of forensic autopsies can proceed as regulated in criminal laws and regulations.